The Progress of High Performance Sintered (Ce,Nd)-Fe-B Magnets Technology - Lei Zhou, Tao Liu, Xiaoning Shi, Hui Wang, Jian Li (Forest Chemicals Review, 1970)
Sintered Nd-Fe-B magnet is widely used for its excellent magnet property. At present,the substitution of Nd with high-abundance Ce has become a research focus for its cost advantage.This paper will introduce the intrinsic property of (Nd,Ce) -Fe-B permanent magnets;phase changes and composition of magnets after the substitution treatment; the impact of element addition and parameter optimization on magnetic phases and micro-structure regulation.The micro-structure and magnetic property of sintered Nd-Fe-B magnets by double main phase method are mainly introduced. And study on magnetic property and corrosion resistance of different content of cerium is highlighted.